Clinically probable paraneoplastic vasculitic peripheral neuropathy in primary central nervous system lymphoma: a case report - Zhuangzhuang Zhang; Chen Ling; Yingshuang Zhang; Weiping Sun; Zhaoxia Wang; Lingchao Meng (BMC Neurology)
Abstract Primary central nervous system lymphoma (PCNSL) is a malignant tumor known to cause direct mass effects and various paraneoplastic syndromes. However, paraneoplastic vasculitic peripheral neuropathy is rarely associated with PCNSL. In this case report, we describe a patient with PCNSL who presented with probable paraneoplastic vasculitic peripheral neuropathy. The patient initially experienced recurrent pain and weakness in bilateral lower limbs for two years, followed by a sudden decline in consciousness over two days. A biopsy of the right sural nerve revealed probable vasculitic peripheral neuropathy, and the diagnosis of PCNSL was confirmed through brain biopsy.